Статистичне забезпечення розвитку менеджмента академічною школою професора O.Г. Лібермана - Кущенко, Олена Іванівна; Назарова, Олександра Юріївна; Чуприна, Олена Анатоліївна; Kushchenko, О.I. (Boston: Primedia eLaunch, 2022)
У статті розглядаються послідовники видатного ученого професора О.Г. Лібермана, які викладали на кафедрі статистики та зробили великий внесок у сучасні економічні реформи в Україні та у інших країнах Східної Європи.

The article considers the followers of the prominent scientist Professor E.G. Lieberman, who lectured at the department of statistics made great contribution to modern economic reforms in the Ukraine and other countries of Eastern Europe.
Statistical providing of drvelopment of management by academic school of professor O.G.Libermana
Title of the monograph - Scientific Foundations in Economics and Management. Section - Management.
Keywords: Lieberman E.G.; followers; statistical research methods of production; economic reforms; Ліберман О.Г.; послідовники; статистичні методи дослідження виробництва; економічні реформи